Evaluasi Tempat Penampungan Sementara (TPS) Sampah (Studi Kasus: Kota Bandung) - Halomoan, Nico; Indrayanti, Sarah Nisrina (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2023)
Bandung City is one of the highest solid waste-producing cities in Indonesia. Waste management needs to be organized so that the waste produced does not harm urban areas. One example of waste management is providing temporary waste storage sites (TPS) as intermediate transfer stations. One hundred fifty-six permanent TPS operates in Bandung, spread over 30 sub-districts with various conditions, both running well and unsuitable conditions affecting waste handling. This study aims to identify the condition of TPS waste management in the city of Bandung and evaluate it based on technical criteria for appropriate TPS buildings. The method for assessing the feasibility of TPS is assessed using 17 criteria, including criteria for TPS buildings and facilities. The evaluation was carried out at 44 TPS in Bandung. The evaluation results show seven criteria for transfer stations with a high degree of conformity and ten for a low level of conformity. The evaluation results resulted in the need for efforts to improve and develop TPS so that it can be used according to the criteria.